Adhesive, pole piece tape and lithium ion battery using the same
By using specific formula adhesives of ethylene, acrylate and maleic anhydride copolymer components, the problem of insufficient bonding performance of existing adhesives in the working temperature range of lithium-ion batteries is solved, and strong bonding performance and electrode sheet protection effect are achieved at high and low temperatures, which improves the safety and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202311447943.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-11-01
AI Technical Summary
The existing adhesive cannot maintain good bonding performance within the operating temperature range of lithium-ion batteries, resulting in insufficient protection of the pole sheet and easy short circuit.
Adhesives made of specific formulations of ethylene components, acrylate components and maleic anhydride copolymer components, maintain strong bonding properties at high and low temperatures and are applied to the electrode sheets of lithium-ion batteries through electrode sheet tape.
This adhesive maintains excellent bonding performance at high and low temperatures, can effectively protect the pole sheet of lithium-ion battery, reduce the risk of short circuit, and improve the safety and stability of the battery.
Smart Images

Figure CN117603635B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer compound compositions, and in particular to an adhesive and a pole piece tape and a lithium ion battery using the adhesive. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, large storage capacity, long cycle life, high energy density, and wide operating temperature range. They are widely used in consumer electronics such as smartphones, laptops, and drones. With the rapid development of the economy and the advancement of modern science and technology, the lithium-ion battery industry has also increased its requirements for lithium-ion batteries, especially the safety and stability of lithium batteries.
[0003] Battery tabs are an important component in lithium-ion batteries. Batteries are divided into positive and negative electrodes. Tabs are metal conductors that lead the positive and negative electrodes out of the battery cell. Simply put, the tabs of the positive and negative poles of the battery are the contact points during charging and discharging. In order to avoid short circuits between the tabs of the positive and negative poles during battery packaging, the pole piece needs to be insulated. However, the adhesives on the market cannot maintain good bonding performance within the operating temperature range of the battery, and cannot maintain protection for the pole piece.
[0004] Therefore, it is necessary to prepare an adhesive that can maintain strong bonding properties at high and low temperatures. Summary of the invention
[0005] The object of the present invention is to provide an adhesive and a pole piece tape and a lithium ion battery using the same, wherein the adhesive has excellent viscosity and can maintain strong bonding performance at both high and low temperatures.
[0006] According to the first aspect of the present invention, an adhesive is provided, which includes 5-15wt% of an ethylene component, 30-50wt% of an acrylate component, and 40-60wt% of a maleic anhydride copolymer component; wherein the ethylene component includes polyethylene, the acrylate component includes polyvinyl acetate, and the maleic anhydride copolymer component includes a maleic anhydride copolymer. After many experiments and explorations by the inventors, it was found that the adhesive prepared by the above formula has excellent viscosity, and can maintain strong adhesion when the amount of adhesive applied is small. The ethylene component, acrylate component, and maleic anhydride copolymer component used in the above formula can be directly purchased commercial materials, or can be modified materials further prepared by specific reactions. Secondly, in the industry terms commonly used in this field, the definition of acrylate is the general term for esters of acrylic acid and its homologues, so polyvinyl acetate can be classified into the acrylate component. Moreover, compared with commercially available adhesives, the adhesive prepared by the present invention also has the advantages of high and low temperature resistance, good tensile strength, and good flexibility, and can maintain excellent bonding performance at both high and low temperatures, so that the adhesive and the bonded material fit well and are tightly bonded, and are not easy to fall off.
[0007] Preferably, the raw material of the ethylene component includes 50-70 wt% polyethylene, 10-30 wt% polyethyl acrylate, and 10-30 wt% polyvinyl alcohol, and the density of polyethylene is 0.910-0.925 g / cm 3 ; and / or, the raw materials of the acrylic ester component include 50-70wt% of polyvinyl acetate, 10-30wt% of ethyl acrylate, and 10-30wt% of ethylene-methacrylic acid copolymer; and / or, the raw materials of the maleic anhydride copolymer component include 50-70wt% of poly(methyl vinyl ether maleic anhydride), 20-40wt% of maleic anhydride-ethylene copolymer, and 5-15wt% of glycidyl methacrylate.
[0008] When the ethylene component of the above formula is used to prepare the adhesive, the compatibility between the ethylene component, the acrylate component and the maleic anhydride copolymer component in the adhesive raw material can be improved, which is beneficial to the preparation of the adhesive. 3 Polyethylene of this type is often referred to as low-density polyethylene in the technical field. The adhesive made by using the acrylic ester component of the above formula has better high-temperature and low-temperature resistance, so that the adhesive has excellent bonding performance at high and low temperatures. Compared with the commercially available maleic anhydride copolymer, the maleic anhydride copolymer component that meets the above formula has a better degree of crosslinking, which can not only improve the processing performance of the adhesive, but also help to improve the flexibility and viscosity of the adhesive, and improve the yield rate of the adhesive.
[0009] Preferably, the ethylene component is prepared by the following steps: mixing the raw materials of the ethylene component at a temperature of 180-230°C for 1-2 hours, and then cooling the reaction mixture to prepare the ethylene component. The raw materials of the ethylene component of the above formula are reacted at a specific temperature of 180-230°C, so that the formula materials can undergo a cross-linking reaction, and the reaction activity is high. The prepared ethylene component can provide better compatibility in the adhesive, and the prepared adhesive has good bonding performance with the surface of most metal materials.
[0010] Preferably, the acrylate component is prepared by the following steps: mixing the raw materials of the acrylate component at a temperature of 180-230° C. for 1-2 hours, and then cooling the mixture obtained by the reaction to obtain the acrylate component. When the raw materials of the acrylate component of the above formula are reacted at 180-230° C. for 1-2 hours, the obtained acrylate component can have better high and low temperature resistance.
[0011] Preferably, the maleic anhydride copolymer component is prepared by the following steps: mixing the raw materials of the maleic anhydride copolymer component at a temperature of 180-230° C. for 1-2 hours, and then cooling the mixture obtained by the reaction to form the maleic anhydride copolymer component. The maleic anhydride copolymer component prepared by the above preparation method has a higher degree of crosslinking and good compatibility with other material components of the adhesive. The adhesive prepared by using the maleic anhydride copolymer component has better flexibility and mechanical processing performance.
[0012] Preferably, the adhesive is prepared by the following steps: preheating and mixing the raw materials for preparing the adhesive at 80-150° C. for 2-4 seconds, and melt-blending the obtained mixture at 220-290° C. for 3-6 seconds to obtain the adhesive.
[0013] Preferably, the adhesive is prepared by the following steps: the raw materials for preparing the adhesive are heated and mixed at 80°C, 150°C, 200°C, 250°C and 290°C in sequence, with a total heating time of 5 to 10 seconds, to obtain the adhesive.
[0014] Preferably, the melt index of the adhesive at 190±2°C is 80-95g / 10min. The inventors have found in their long-term experiments and explorations that by adjusting the raw material formula and molecular weight of the adhesive so that the melt index of the adhesive is within the above range, it is beneficial to reduce the defective rate of the adhesive product, and the prepared adhesive can have good tensile strength and flexibility. If the melt index of the adhesive is too small, the fluidity of the adhesive in the molten state is poor, which is not conducive to processing, and there is a risk of non-film formation; if the melt index of the adhesive is too large, the fluidity of the adhesive in the molten state is good, which is also not conducive to processing, and there is a risk of collapse.
[0015] According to the second aspect of the present invention, a pole piece tape is provided, comprising a substrate and an adhesive layer arranged on the surface of the substrate, wherein the adhesive layer is made of the above-mentioned adhesive. In the assembly and production process of lithium-ion batteries, ceramic insulating coatings are generally used to fix, insulate and protect the pole piece parts of lithium-ion batteries. In the industry, polyvinylidene fluoride mixed nano-ceramic slurry is commonly used to prepare ceramic insulating coatings. However, in the process of preparing batteries, the electrode materials need to be stacked or wound. At this time, the ceramic insulating coating coated on the surface of the electrode material is prone to cracking or even falling off from the pole piece material, thereby affecting the fixation and protection of the pole piece. In addition, there are more volatile organic compounds in the process of producing ceramic insulating coatings, and the product defect rate is high. The inventors of the present application use the above-mentioned high and low temperature resistant adhesive and good bonding performance to prepare pole piece tapes, which can fix the internal pole piece and external circuit for the battery. Even if the electrode material has undergone a stacking or winding process, the pole piece can still be effectively wrapped, reducing the possibility of burrs on the electrode material piercing the diaphragm, thereby avoiding battery short circuit. Secondly, the electrode tape has excellent flexibility and insulation, and is resistant to high and low temperatures and electrolyte corrosion. It can still have good adhesion performance in extreme environments and can provide good wrapping for the electrode to avoid leakage or short circuit. In particular, the electrode tape provided by this solution can be applied to positive electrode materials or negative electrode materials. For different electrode materials, the electrode tape can provide good protection and insulation effects.
[0016] Preferably, the substrate is selected from at least one of a polyester film and a polyethylene film. When a polyester film (PET) or a polyethylene film (PE) is used as the substrate, the adhesive layer in the pole piece tape can be tightly bonded to the substrate, and the substrate has good insulation performance. The pole piece tape is not easy to fall off between the substrate and the adhesive layer during use, thereby ensuring that the pole piece tape maintains excellent insulation during use.
[0017] Preferably, the substrate is selected from at least one of biaxially oriented polyester film and biaxially oriented polyethylene film. When the substrate is biaxially oriented polyester film (BOPET) or biaxially oriented polyethylene film (BOPE), the pole piece tape has better insulation performance and flexibility, and can maintain good adhesion performance at -60℃ to 120℃, so that the product use temperature of the pole piece tape can meet the operating temperature range of most lithium batteries. Secondly, when the density is selected to be 0.910~0.925g / cm 3 When 50-70wt% of polyethylene, 10-30wt% of polyethyl acrylate and 10-30wt% of polyvinyl alcohol are used as the ethylene components in the adhesive, the prepared adhesive has good compatibility with BOPET and BOPP, and can make the adhesive layer of the electrode tape fit tightly to the substrate, which is conducive to the close fitting and tight wrapping of the electrode.
[0018] Preferably, the substrate is a biaxially oriented polyester film. Compared with the electrode tape made of BOPE as the substrate, the electrode tape made of BOPET as the substrate has a smaller thickness, can provide sufficient strength to protect the electrode, can also avoid the electrode tape from being too thick, can reduce the space occupied by the electrode tape, and improve the energy density of the battery.
[0019] Preferably, the pole piece tape is prepared by the following steps: preheating and mixing the raw materials for preparing the adhesive layer at 80-150°C for 2-4 seconds, melt blending the obtained mixture at 180-230°C for 3-6 seconds, coating the obtained melt on the substrate, and then cooling and shaping the melt and the substrate to obtain the pole piece tape. The inventor prepared the above-mentioned pole piece tape by co-extrusion process, which not only has a simple production process, mild preparation conditions, good economic benefits, but also the production process fully meets the domestic environmental protection and safety requirements.
[0020] Preferably, the pole piece tape is prepared by the following steps: the raw materials for preparing the adhesive layer are heated and mixed at 80°C, 150°C, 200°C, 250°C, and 290°C in sequence, with a total heating time of 5 to 10 seconds, and the obtained melt is coated on the substrate, and then the melt and the substrate are cooled and shaped at 10 to 30°C to obtain the pole piece tape. By heating the raw materials for preparing the adhesive layer in sequence, the obtained pole piece tape can have better viscosity and can be closely adhered to the pole piece material.
[0021] Preferably, the thickness of the pole piece tape is 12 to 20 μm, and the ratio of the thickness of the adhesive layer to the thickness of the substrate is 1 to 1.5:1. The inventor can make the thickness of the pole piece tape 12 to 20 μm, and the ratio of the thickness of the adhesive layer to the thickness of the substrate be 1 to 1.5:1 by adjusting the coating thickness of the adhesive and the thickness of the substrate. Compared with the pole piece coatings commonly used in the industry or commercially available pole piece tapes, the above-mentioned pole piece tape is lighter and thinner, and plays an important role and significance in building batteries with high energy density. Moreover, within this thickness range, the pole piece tape can still provide good protection for the pole piece material, reduce the possibility of material burrs causing damage to battery products, and avoid accidents caused by loose adhesion of the pole piece tape leading to electrolyte leakage.
[0022] Preferably, the width of the pole piece tape is 5 to 8 mm.
[0023] According to a third aspect of the present invention, a lithium-ion battery is provided, the lithium-ion battery comprising a pole piece and the pole piece tape, at least a portion of the pole piece tape is attached to the surface of the pole piece. By using the pole piece tape, the safety and stability of the lithium-ion battery can be improved, and the goal of reducing the weight of the lithium-ion battery can be achieved, so as to obtain a lithium-ion battery with high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of the electrode tape provided by the present invention, and the corresponding relationship between the figure numbers is: 1. Adhesive layer; 2. Substrate. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment provides a pole piece tape, including a substrate 2 and an adhesive layer 1 arranged on the surface of the substrate 2, wherein the adhesive layer 1 is made of the following adhesive; the substrate 2 is a biaxially oriented polyester film (BOPET).
[0028] The adhesive comprises 10 wt% of ethylene components, 40 wt% of acrylic ester components, and 50 wt% of maleic anhydride copolymer components. The specific preparation method is as follows:
[0029] (1) Raw materials for preparing adhesive:
[0030] The ethylene component includes a density of 0.910 to 0.925 g / cm 3 60wt% of polyethylene (i.e., low-density polyethylene, LDPE), 20wt% of polyethyl acrylate (PEA), and 20wt% of polyvinyl alcohol (PVA). The three materials are mixed in a co-extrusion device according to a ratio, heated at 200°C for 1.5 hours, extruded, cooled at 20°C for shaping, and pelletized to obtain an ethylene component.
[0031] The acrylic ester component comprises 60 wt% of polyvinyl acetate (PVAc), 20 wt% of ethyl acrylate (EA), and 20 wt% of ethylene-methacrylic acid copolymer (EMA). The three materials are mixed in a co-extrusion device according to a proportion, heated at 200° C. for reaction for 1.5 hours, extruded, cooled at 20° C. for shaping, and pelletized to obtain the acrylic ester component.
[0032] The maleic anhydride copolymer component comprises 60 wt% of poly(methyl vinyl ether maleic anhydride) (i.e., P(MVE-MA)), 30 wt% of maleic anhydride-ethylene copolymer (P(E-MA)), and 10% of glycidyl methacrylate (GMA). The three materials are mixed in a co-extrusion device according to a proportion, heated at a temperature of 200° C. for reaction for 5 seconds, extruded, cooled at 20° C. for shaping, and pelletized to obtain the maleic anhydride copolymer component.
[0033] (2) Preparation of electrode tape:
[0034] The above-mentioned ethylene component, the above-mentioned acrylate component, and the above-mentioned maleic anhydride copolymer component are fed into the co-extrusion equipment according to the proportion, and heated and mixed at 80°C, 150°C, 200°C, 250°C, and 290°C in sequence, with a total heating time of 5 seconds to obtain an adhesive. At 290°C, the adhesive is applied to the substrate, and then cooled and shaped at 20°C to form an adhesive layer 1 to obtain a pole piece film. The pole piece film is cut into 7mm pieces to obtain a pole piece tape.
[0035] In the electrode tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 6 μm. The specific structural diagram is as follows: Figure 1 shown.
[0036] Example 2
[0037] Experimental Group 2-1
[0038] This experimental group refers to the preparation method provided in Example 1 to prepare a pole piece tape. The difference between this experimental group and Example 1 is that in the process of preparing the ethylene component, high-density polyethylene (HDPE) of equal mass is used to replace the low-density polyethylene in Example 1. The density of the high-density polyethylene used in this example is 0.941-0.965 g / cm 3 The remaining raw materials and preparation methods are strictly consistent with those in Example 1.
[0039] Experimental group 2-2
[0040] This experimental group prepared a pole piece tape by referring to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the process of preparing the acrylic ester component, an equal mass of polyethyl acrylate (PEA) was used to replace the ethyl acrylate in Example 1. The rest of the raw materials and preparation method were strictly consistent with Example 1.
[0041] Experimental Group 2-3
[0042] This experimental group prepared a pole piece tape by referring to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the process of preparing the maleic anhydride copolymer component, an equal mass of polypropylene-maleic anhydride copolymer (AA / MA) was used to replace the poly(methyl vinyl ether maleic anhydride) in Example 1. The rest of the raw materials and preparation method were strictly consistent with Example 1.
[0043] Experimental Groups 2-4
[0044] This experimental group provides a pole piece tape, including a substrate 2 and an adhesive layer 1 arranged on the surface of the substrate 2, and the adhesive layer 1 is made of the following adhesive.
[0045] The adhesive comprises 10 wt% of ethylene component, 40 wt% of acrylate component and 50 wt% of maleic anhydride copolymer component. 3 The polyethylene; the acrylic ester component is polyvinyl acetate; and the maleic anhydride copolymer component is poly(methyl vinyl ether maleic anhydride).
[0046] The specific preparation method of the electrode tape is as follows:
[0047] The above-mentioned ethylene component, the above-mentioned acrylate component, and the above-mentioned maleic anhydride copolymer component are fed into the co-extrusion equipment (extruder) according to the proportion, and heated and mixed at 80°C, 150°C, 200°C, 250°C, and 290°C in sequence, with a total heating time of 5 seconds to obtain an adhesive. At 290°C, the adhesive is applied to the substrate, and then cooled and shaped at 20°C to form an adhesive layer 1 to obtain a pole piece film. The pole piece film is cut into 7mm pieces to obtain a pole piece tape. In the pole piece tape, the thickness of the substrate 2 is 6μm, and the thickness of the adhesive layer 1 is 6μm.
[0048] Experimental Groups 2-5
[0049] This experimental group prepared a pole piece tape with reference to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that: in the process of preparing the pole piece tape, the raw materials used to prepare the pole piece tape are fed into the co-extrusion equipment according to the ratio, and heated and mixed at 260°C. The total heating time is 5 seconds to obtain an adhesive. At 260°C, the adhesive is applied to the substrate, and then cooled and shaped at 20°C to form an adhesive layer 1 to obtain a pole piece film. The pole piece film is cut into 7mm to obtain a pole piece tape. The remaining raw materials and preparation methods are strictly consistent with Example 1.
[0050] Experimental Groups 2-6
[0051] This experimental group prepared a pole piece tape with reference to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the process of preparing the pole piece tape, the raw materials of the ethylene component, the raw materials of the acrylate component, and the raw materials of the maleic anhydride copolymer component are directly fed into the co-extrusion equipment according to the ratio to prepare the pole piece tape. This is equivalent to not using the step-by-step preparation method of Example 1 in which the ethylene component, the acrylate component, and the maleic anhydride copolymer component are first prepared, and then the adhesive is prepared, but forming in one step. The rest of the raw materials and preparation methods are strictly consistent with Example 1.
[0052] Example 3
[0053] Experimental Group 3-1
[0054] This experimental group prepared a pole piece tape by referring to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The other raw materials and preparation methods are strictly consistent with Example 1.
[0055] Experimental group 3-2
[0056] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-1. The difference between this experimental group and the experimental group 2-1 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-1.
[0057] Experimental group 3-3
[0058] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-2. The difference between this experimental group and the experimental group 2-2 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-2.
[0059] Experimental Group 3-4
[0060] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-3. The difference between this experimental group and the experimental group 2-3 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-3.
[0061] Experimental Groups 3-5
[0062] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-4. The difference between this experimental group and the experimental group 2-4 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-4.
[0063] Experimental Groups 3-6
[0064] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-5. The difference between this experimental group and the experimental group 2-5 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-5.
[0065] Experimental Groups 3-7
[0066] This experimental group prepared a pole piece tape by referring to the preparation method provided by the experimental group 2-6. The difference between this experimental group and the experimental group 2-6 is that in the prepared pole piece tape, the thickness of the substrate 2 is 6 μm, and the thickness of the adhesive layer 1 is 9 μm. The rest of the raw materials and preparation methods are strictly consistent with those of the experimental group 2-6.
[0067] Example 4
[0068] Experimental Group 4-1
[0069] This experimental group prepared a pole piece tape by referring to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the process of preparing the pole piece tape, a biaxially oriented polyethylene film (BOPE) is used as the substrate. The rest of the raw materials and preparation method are strictly consistent with Example 1.
[0070] Experimental Group 4-2
[0071] This experimental group prepared a pole piece tape by referring to the preparation method provided in Example 1. The difference between this experimental group and Example 1 is that in the process of preparing the pole piece tape, a biaxially oriented polypropylene film (BOPP) is used as the substrate. The rest of the raw materials and preparation method are strictly consistent with Example 1.
[0072] Comparative Example 1
[0073] This comparative example refers to the preparation method provided in Example 1 to prepare a pole piece tape. The difference between this comparative example and Example 1 is that in the process of preparing the adhesive, polypropylene of equal mass is used to replace the ethylene component in Example 1. The other raw materials and preparation method are strictly consistent with Example 1.
[0074] Comparative Example 2
[0075] This comparative example refers to the preparation method provided in Example 1 to prepare a pole piece tape. The difference between this comparative example and Example 1 is that in the process of preparing the adhesive, an equal mass of polyethyl acrylate is used to replace the acrylic ester component in Example 1. The other raw materials and preparation methods are strictly consistent with Example 1.
[0076] Comparative Example 3
[0077] This comparative example refers to the preparation method provided in Example 1 to prepare a pole piece tape. The difference between this comparative example and Example 1 is that in the process of preparing the adhesive, the addition of the maleic anhydride copolymer component is omitted, and the adhesive includes an ethylene component and an acrylate component, and the mass ratio of the ethylene component to the acrylate component is consistent with that in Example 1, which is 1:4. The remaining raw materials and preparation methods are strictly consistent with those in Example 1.
[0078] Test Case
[0079] Test objects: The electrode tapes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used as test objects.
[0080] Test items:
[0081] (1) Adhesion: The test object was cut into strips with a width of 7 mm and a length of 10 mm, and attached to a steel plate. The test was carried out in accordance with GB T7124-2008 Determination of tensile shear strength of adhesives.
[0082] (2) High temperature resistance: The test object was attached to a steel plate and placed at 100°C for 2 hours. The adhesion test was then performed to measure the adhesion of the electrode tape after soaking in electrolyte.
[0083] (3) Brittleness performance: The adhesive used by the test object was prepared into a test adhesive layer with a thickness of 6 μm according to the preparation method provided in Example 1. Each test adhesive layer was placed in a nitrogen environment, and a tensile force test was performed on the test object at a temperature of -20°C. The tensile force at which the test object became brittle was recorded.
[0084] (4) Insulation performance: The test object was assembled on the tab of a 4.48V high energy density lithium-ion battery and charged and discharged for 500 times. The battery was dismantled and the appearance of the voltage and electrolyte resistant electrode tape was observed.
[0085] Test results: The raw material formula, preparation method and product structure of each test object are shown in Table 1. The test results are shown in Table 2.
[0086] Table 1. Raw material formula, preparation method and product structure of each test object
[0087]
[0088]
[0089] Table 2. Test results of the subjects
[0090]
[0091] Result analysis:
[0092] Comparing the electrode tapes provided in Examples 1 to 4 with those in Comparative Examples 1 to 3, it can be seen from the test data shown in Table 2 that the electrode tapes provided in Examples 1 to 4 have better adhesion and insulation properties than the electrode tapes in Comparative Examples 1 to 3. It can be explained that the adhesive prepared by using the ethylene component including polyethylene, the acrylate component including polyvinyl acetate, and the maleic anhydride copolymer component including maleic anhydride copolymer has the advantages of better high and low temperature resistance, good tensile strength, and good flexibility, and can maintain excellent bonding properties at both high and low temperatures, so that the adhesive and the bonded material are well bonded and tightly bonded, and are not easy to fall off.
[0093] By comparing the electrode tapes provided in Examples 1-2 with those in Example 3, it can be found that as the thickness of the adhesive layer 1 increases, the viscosity of the electrode tape also increases. However, compared with the electrode tape of Example 3, the electrode tapes of Examples 1-2, which have a thinner thickness of the adhesive layer 1, also have excellent bonding effects.
[0094] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An adhesive, characterized in that: The adhesive comprises 5-15 wt% of an ethylene component, 30-50 wt% of an acrylate component, and 40-60 wt% of a maleic anhydride copolymer component; The raw materials of the ethylene component include 50-70 wt% polyethylene, 10-30 wt% polyethyl acrylate, and 10-30 wt% polyvinyl alcohol, and the density of the polyethylene is 0.910-0.925 g / cm 3 ; The raw materials of the acrylic ester component include 50-70 wt% polyvinyl acetate, 10-30 wt% ethyl acrylate, and 10-30 wt% ethylene-methacrylic acid copolymer; The raw materials of the maleic anhydride copolymer component include 50-70 wt % of poly(methyl vinyl ether maleic anhydride), 20-40 wt % of maleic anhydride-ethylene copolymer, and 5-15 wt % of glycidyl methacrylate.
2. The adhesive according to claim 1, characterized in that: The ethylene component is prepared by the following steps: mixing the raw materials of the ethylene component at a temperature of 180-230° C. for 1-2 hours, and then cooling the mixture obtained by the reaction to prepare the ethylene component.
3. The adhesive according to claim 1, characterized in that: The acrylic ester component is prepared by the following steps: mixing the raw materials of the acrylic ester component at a temperature of 180-230° C. for 1-2 hours, and then cooling and shaping the reaction mixture to obtain the acrylic ester component.
4. The adhesive according to claim 1, characterized in that: The maleic anhydride copolymer component is prepared by the following steps: mixing the raw materials of the maleic anhydride copolymer component at a temperature of 180-230° C. for 1-2 hours, and then cooling the mixture obtained by the reaction to prepare the maleic anhydride copolymer component.
5. The adhesive according to any one of claims 1 to 4, characterized in that: The adhesive has a melt index of 80-95 g / 10 min at 190±2°C.
6. A pole piece tape, characterized in that: It comprises a substrate and an adhesive layer arranged on the surface of the substrate, wherein the adhesive layer is made of the adhesive according to any one of claims 1 to 5.
7. The pole piece tape as claimed in claim 6, characterized in that: The substrate is selected from at least one of a polyester film and a polyethylene film.
8. The pole piece tape as claimed in claim 6, characterized in that: Prepared by the following steps: The raw materials for preparing the adhesive layer are preheated and mixed at 80-150° C. for 2-4 seconds, the obtained mixture is melt-blended at 220-290° C. for 3-6 seconds, and the obtained melt is coated on the substrate, and then the melt and the substrate are cooled and shaped to obtain a pole piece tape.
9. The pole piece tape according to claim 6, characterized in that: The thickness of the electrode tape is 12-20 μm, and the ratio of the thickness of the adhesive layer to the thickness of the substrate is 1-1.5:
1.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a pole piece and a pole piece tape as claimed in any one of claims 6 to 9, wherein at least a portion of the pole piece tape is adhered to the surface of the pole piece.
Citation Information
Patent Citations
Laminate film
JP1999315257A